Pengaruh Penggunaan Media Foam Art terhadap Kreativitas Anak - Poja Okta Sutria Elisa; Rivda Yetti (Jurnal Halaqah, 2020)
This research is based on the importance of developing creative skills in early childhood. Creativity is a person's ability to create something new, unique, different from the previous one, and original in the form of ideas and real work which is the result of creative and imaginative thinking. This study aims to determine the effect of using foam art media on the development of children's creativity. This research method is to use a literature study. A literature study is a research whose data collection comes from books, newspapers, magazines, articles, journals, and other sources that are appropriate with the study material. The research findings show that foam art media can improve the creative ability of early childhood. Children's creativity can be trained since childhood, by making creative creations from foam art, inviting children to make creative creations from foam art will be a fun activity for children. Foam art is a material that is soft and safe for children, easily shaped, and has a variety of striking colors that are suitable for developing children's creativity. Thus the foam art media can improve children's creative abilities.